Varied presentations of congenital ocular synkinesis: do they all fit congenital cranial dysinnervation disorder spectrum? - Curi,Ian (2021)
ABSTRACT Purpose: Synkinesis results from nerve miswirings and causes aberrant movements of the affected muscles. We present a series of cases of rare congenital ocular synkinesis involving the extraocular muscles and the levator palpebrae superioris and speculate the possibility of classifying these entities in the spectrum of congenital cranial dysinnervation disorder. Methods: Records of patients with the diagnosis of congenital ocular synkinesis were analyzed retrospectively. We analyzed the sex, laterality, and complete features of the ocular motility of each patient. Results: Nine patients with congenital ocular synkinesis were included. A slight predominance of women was noted. In terms of laterality, four patients had only the right eye involved, four had only the left eye, and one had both eyes involved. Notably, 55.5% were orthotropic in the primary position. The third, fourth, and sixth cranial nerves were involved in the miswiring in 100%, 44.4%, and 11.1% of the cases, respectively. Conclusions: Congenital synkinesis might present in a very eclectic and uncommon fashion. The aberrant innervation in these cases classifies them into the group of congenital cranial dysinnervation disorders.